Potential use of cerebrospinal fluid serotonin level as a marker of neuronal injury after exposure to 3, 4-Methylenedioxymethamphetamine - Fatin Haniza Zakariaa,c, Nor Hidayah Abu Bakarb,c, Nasir Mohamadb,c (Journal of Applied Pharmaceutical Science, 2017)
No abstract available.
Keywords: Serotonin, neuronal injury, MDMA, Drug abuse.